Prognosis of Transcatheter Closure Compared with Surgical Repair of Paravalvular Leak after Prosthetic Valve Replacement: A Retrospective Comparison - Yang, Chun; Liu, Yang; Tang, Jiayou; Jin, Ping; Li, Lanlan; Yu, Shiqiang; Yang, Jian (The Thoracic and Cardiovascular Surgeon, 2020)
Objective Paravalvular leak (PVL) after valve replacement remains clinically challenging. Percutaneous closure is an effective therapy for patients with PVLs because reoperation is associated with high rates of morbidity and mortality. The purpose of this study was to retrospectively compare the clinical outcome of transcatheter closure and surgical repair in patients with a PVL.Methods From January 2000 to May 2016, 131 patients with PVL were treated at three major medical centers in China. Perioperative characteristics and outcomes of the procedure were reviewed.Results Sixty-eight (51.9%) patients with PVLs were treated with percutaneous transcatheter closure (group I). The procedure was successful in 67 (98%) with no hospital deaths. Sixty-three (48.1%) patients with PVLs had a reoperation (group II). Five of the surgical patients had a third open-heart operation for residual regurgitation, and one underwent successful percutaneous closure. Six patients died in the hospital postoperatively. All patients in group II but only 11 in group I needed perioperative blood transfusions. The procedural time and hospital stay after the procedure were significantly shorter in group I than in group II. At the 1-year follow-up, cardiac function improved by ≥ 1 New York Heart Association functional class in 55 (82%) patients in group I and in 39 (68%) patients in group II.Conclusions Transcatheter closure was shown to be a safe, effective therapeutic option in patients with PVL. It was associated with a lower hospital mortality rate, shorter procedural time, and fewer blood transfusions than surgical treatment in selected patients.
Keywords: paravalvular leak; valve replacement; transapical; transcatheter; surgery; follow-up